2011
DOI: 10.1080/15222055.2011.588918
|View full text |Cite
|
Sign up to set email alerts
|

Chloramine‐T Margin‐of‐Safety Estimates for Fry, Fingerling, and Juvenile Rainbow Trout

Abstract: Chloramine-T (CLT) is a candidate for approval for use in U.S. aquaculture to control mortality in freshwaterreared salmonids caused by bacterial gill disease (causative agent, Flavobacterium branchiophilum). The proposed treatment regimen is to administer CLT at 12-20 mg/L in a static or flow-through bath for 60 min/d on three alternate or consecutive days. To estimate a CLT margin of safety, defined as the highest dosing regimen above the proposed maximum therapeutic regimen at which no adverse effects are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Survival of fingerling Channel Catfish Ictalurus punctatus with columnaris was significantly improved after being treated with HP at 50, 75, or 100 mg/L of water for 60 min/d on three alternate days, but these fish did not exhibit sensitivity to the higher doses (Rach et al 2003). Results from these studies suggest varying sensitivity to CLT and HP and a "Goldilocks paradigm" (i.e., CLT and HP doses that are too low or too high may yield less desirable results than one that is just right for the species or lifestage; Gaikowski et al 1999;Russo et al 2007;Gaikowski et al 2008;Bowker et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Survival of fingerling Channel Catfish Ictalurus punctatus with columnaris was significantly improved after being treated with HP at 50, 75, or 100 mg/L of water for 60 min/d on three alternate days, but these fish did not exhibit sensitivity to the higher doses (Rach et al 2003). Results from these studies suggest varying sensitivity to CLT and HP and a "Goldilocks paradigm" (i.e., CLT and HP doses that are too low or too high may yield less desirable results than one that is just right for the species or lifestage; Gaikowski et al 1999;Russo et al 2007;Gaikowski et al 2008;Bowker et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…In this work, F. psychrophilum is much more resistant to chloramine-T since 300 ppm were needed to inhibit the bacterial growth and only severe chloramine-T treatments ranging from 400 to 1,200 ppm (for about 1 hr to 5 min, respectively) were bactericidal. Experiments performed to evaluated chloramine-T as possible candidate for approval for use to control mortality in freshwater-reared salmonids caused by bacterial gill disease have been shown that the fry and fingerlings viability was unaffected by exposure to concentrations less than 100 and 60 ppm, respectively [30]. Clearly, rainbow trout eggs are much more resistant to chloramine-T since none of the 20-min treatments of chloramine-T up to 1,200 ppm did reduce significantly the egg viability.…”
Section: Discussionmentioning
confidence: 99%
“…Following the USGS (2007) and FDA (2015) recommendations, a dose of 80 mg OTC kg −1 body wt of fish daily for 10 days was taken as the minimum dose of the drug for the establishment of its safety. So, for safety evaluation, the drug was administered at a maximum 10 times of the minimum treatment dose and three times of the treatment duration following Bowker et al (2011).…”
Section: Introductionmentioning
confidence: 99%